Modeling soil electrical conductivity under impulse discharge for electrical ground system - Fajingbesi, Fawwaz Eniola; Midi, Nur Shahida; Yusoff, Siti Hajar; Elsheikh, Elsheikh Mohamed Ahmed (Institute of Research Engineers and Doctors, 2018)
Soil electrical conductivity play an essential role in proper grounding system design for dissipation of static and dynamic electric charge. However, soil properties such as pH, moisture and nutrients causes’ non-linear variation in the soil electrical conductivity. This non-linear soil impedance phenomena directly affect electrical modeling of soil characteristics for efficient grounding system design. In this paper, the electrical dependency of soil properties on overall impedance have been investigated and used to formulate a soil impedance electrical circuit equation model through simulation and empirical methods. Electrical conductivity for samples of 30kg of soil with varying properties within at a moisture range of 14%-26% where injected with impulse discharge and the corresponding plot where fitted with electrical circuit simulation until a proper fit was achieved. The result shows that soil electrical impedance can be modeled with a complex circuit having both capacitive, resistive and inductive elements.